Developing Technopreneurs In Asia:A Strategic Management Research Perspective - Milton-Smith, John (2003)
There was a widespread view during the 1990s that technological entrepreneurship in Asia had lagged behind Europe and the United States, as opposed to the more traditional areas in which Asian family businesses have excelled such as property development,retailing and trade,and notwithstanding considerable urging and funding initiatives by governments in the region.The invention of the word 'technopreneur' probably in Singapore was a reflection of just how strong this concern was. It was widely adopted and demonstrated the blinkered, kneejerk reaction of governments and universities in the region attempting to meet the challenge of the so-called 'New Economy'.There was a widely-shared assumption that the revolution in information technology required the invention of a completely new business paradigm. In Asia generally there was a special sense of urgency about the need to redirect entrepreneurial instinct and effort into technological ventures instead of the more traditional areas of entrepreneurship such as retail,trading and property investment activity. The role of a technopreneur was (and is) seen as some one who brings together research talent, venture capital, new business concepts and management skill to create commercially successful technological innovations or, alternatively,to effectively leverage innovations through the application of technology. The aim of this paper is to examine the performance of the technopreneurship phenomenon in Asia and to explore whether the Asian Crisis of 1997-98 and its aftermath offer any useful insights into the context, behaviour and practices of Asian SMEs, which might provide a more general understanding of the conditions in which high technology entrepreneurs are likely to flourish.